The mediating role of emotion on the relationship between festival quality and loyalty / Hassnah Wee - Wee, Hassnah (Institute of Graduate Studies, UiTM, 2016)
Examining the role of event visitors’ emotion towards loyalty has recently increased in the research studies which diminishing the impact of event visitors satisfaction towards loyalty. The outcome of emotion as mediator has resulted a mix findings from past studies. Emotion is said to be a predictor to loyalty in various environment and study setting. Nevertheless, the role of emotion as mediator within the Stimulus- Organism-Response paradigm in event tourism setting is very limited. Therefore, this study intends to validate and expand research areas in festival setting by integrating theories, models, and constructs within the behavioural context of event tourism to explain the complex process of environmental stimuli and visitors’ emotions and loyalty. This study specifically focuses on examining the effect of festival quality (service performance quality and perceived service quality) on visitors’ loyalty directly or indirectly when emotion is the mediating factor. The Stimulus- Organism-Response (SOR) paradigm was the chosen underpinning theory with modified Mehrabian-Russell model was used as the conceptual framework for this study…